Political competition and environmental reporting: Evidence from New Zealand local governments - Mir, M.; Chatterjee, Bikram; Taplin, Ross (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this paper is to investigate the relationship between “political competition” and “environmental reporting” by New Zealand local governments. Design/methodology/approach – The research method includes a longitudinal analysis of environmental reporting by New Zealand local governments in their annual reports for the financial years 2005-2006 to 2009-2010. “Content analysis” was used to attach scores to the extent of environmental reporting. The “number of candidates divided by the number of available positions at the previous election” was used as the proxy for “political competition”. Findings – The study reports a positive relationship between “political competition” and “environmental reporting” in 2007-2008. The number of local governments reporting voluntary environmental information increased in 2006-2007 and 2007-2008 compared to 2005-2006, followed by a reduction in such numbers following the 2007-2008 financial year. This trend in disclosure can be attributed to the local government elections in October 2007. This finding is consistent with the expectation of “agency theory” and provides insight into the pattern of perceived agency costs. The study also finds a dearth in reporting “monetary” and “bad” news. Originality/value – The study contributes towards the previous literature on environmental reporting by concentrating on the public sector and New Zealand, together with investigating the relationship of such reporting with “political competition” through a longitudinal analysis. The theoretical contribution of this study is the adoption of “agency theory” in the context of public sector voluntary reporting and investigating the significance attached by agents to environmental reporting to minimise agency cost. The practical contribution of the study is in the area of future development of reporting standards in regards to environmental reporting.